2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.25647
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Learning through Real-time Tracking Display of Captions

Abstract: Gary has been teaching and directing the Center on Access Technology Innovation Laboratory at NTID for five years. He is a deaf engineer who retired from IBM after serving for 30 years. He is a development engineering and manufacturing content expert. He develops and teaches all related engineering courses. His responsibility as a director of Center on Access Technology Innovation Laboratory include the planning, implementation and dissemination of research projects that are related to the need of accessibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The basis of RTTD-MS comes from the Real-Time Text Display (RTTD) developed by Kushalnagar, et al (R. Kushalnagar et al, 2016). for classroom use.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis of RTTD-MS comes from the Real-Time Text Display (RTTD) developed by Kushalnagar, et al (R. Kushalnagar et al, 2016). for classroom use.…”
Section: Related Workmentioning
confidence: 99%
“…Kushalnagar et al, (Behm, Kushalnagar, Stanislow, & Kelstone, 2015;R. Kushalnagar et al, 2016) found RTTD to be an effective captioning method in the classroom setting, improving students' ability to follow along with a lecture and to understand lecture content over traditional captioning.…”
Section: Related Workmentioning
confidence: 99%
“…RTTD-ID builds on Real-Time Text Display (RTTD) developed by Kushalnagar, et al [11]. for classroom use.…”
Section: Related Workmentioning
confidence: 99%
“…Kushalnagar et al, [11], [12] found RTTD to be an effective captioning method in the classroom setting, improving students' ability to follow along with a lecture and to understand lecture content over traditional captioning. However, the system does not indicate who is speaking.…”
Section: Related Workmentioning
confidence: 99%